Perencanaan Bangunan Pengaman Pantai ( Breakwater ) TPI Ujung Batu Jepara - nur laila sari ayu, wiwit; Ariyanto (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2022)
A structure used to protect the coast from damage due to the attack of sea waves, currents, reduce wave energy reaching the coast and change the rate of sediment transport along the coast. One of the beach protection structures is a breakwater. The breakwater is built to protect the waters behind it against wave attacks. Besides, it is also used to control abrasion that erode the coast. The planning location is on the beach of the Fish Auction Place (TPI) Ujung Batu Jepara, Jalan K.H. Sidiq Harun, Ujung Batu Village, Jepara Regency. With the coordinates -6.582469, 110.656976. This plan calculates the design wave height, dimensions, and analysis of the planned building using the sloping breakwater type. In calculations using the Hudson formula. The first alternative was obtained with a crushed rock weight of 650 kg and a tetrapod of 110 kg, with a protection layer of 1.82 m thick, 2.79 m wide and an elevation of 5.3 m. The second alternative has a material weight of 450 kg and 200 kg of crushed stone for the tetrapod, and has a protective layer thickness of 1.65 m, width of 2.47 m and elevation of 5.2 m. As for the third alternative, the crushed stone was 307.5 kg with a tetrapod of 132.5 kg with a protection layer of 1.44 m thick, 2.2 m wide and 4.75 m elevation.